The Environmental Sensation and its relationship to Spatial Intelligence (Journal of Humanities and Social Sciences Research, 2023)
The research aims to The Environmental Sensation-Spatial Intelligence in Architects in order achieving aims the current research, the researcher used. The Environmental Sensation scale which consists of (37) items and Spatial Intelligence  scale which consists of (30) items in their final form, the research check the psychometric properties such as rarity and reliability for both scales. Then the two scales were applied to a sample of (400) Architects, and by (228) engineers (172) female engineers from the research community State Ministries, The results of the current research indicated, based on the use A number of statistical methods In light of result indicated that The Environmental Sensation and Spatial Intelligence in Architects were higher than average, Meaning the respondents had Environmental Sensation and Spatial Intelligence, T. There is a direct statistically significant relationship between sensitivity and Spatial Orientation only. In light of the indicated results, a number of recommendations and proposals were made for subsequent research.